Establishing the multi-criteria roadmap and metrics for the evaluation of active films for food packaging - Ana Arias (Current Research in Green and Sustainable Chemistry, 2021)
Food industry is one of the sectors with the highest production volume, with disposable plastic films being the most widespread packaging method. The production of these packaging materials is characterized by a linear process, based on an abusive consumption of non-renewable fossil resources and with significant environmental problems. This management model must be modified according to the principles of green and sustainable chemistry: circularity, reduction of waste streams, appropriate use of resources, increase in the useful life of products and use of renewable natural resources. To achieve this, the early stages of product design, which must consider the applicability of the packaging product, its efficiency and its impact on the environment and on the consumer, are crucial. Within this framework, this report provides a roadmap based on holistic criteria together with quantitative metrics to analyze the opportunities and challenges of bioactive food packaging prototypes. Five main categories have been selected for analysis: packaging evaluation, environmental, circularity, economic and social criteria. The multi-decision criteria map will help researchers and stakeholders to examine the suitability of bio-based packaging from environmental, technical and consumer health preservation perspectives.